DEVELOPMENT OF MATHEMATICAL DERIVATIVE BOARD PROPS TO IMPROVE STUDENTS' MATHEMATICAL CONCEPT UNDERSTANDING - Elmania, Putri; Syahirani, Siti; Safitri, Ayu; Lubis, M. Ilyas; Arianto, Arianto (JURNAL EDUSCIENCE, 2024)
The feasibility results were obtained based on the results of the validation questionnaire for the mathematics derivative board props for each validator, namely media experts, who obtained a percentage result of 78.24% in the "Good" category. The material expert obtained a percentage result of 86% in the "Very Good" category. Small group students obtained a percentage result of 83.5% in the "Very Good" category. The average percentage of the three validators is 82.63% in the "Very Good" category. In this way, the mathematics-derived board teaching aids are declared suitable for use in the learning process. This result is based on the average pretest score of 40.5 and the average posttest data result is 83.5 and the N-Gain calculation is 0.72 with the interpretation "High" so it can be said that there is an increase in understanding of mathematical concepts.Keywords: tools display; board derivative mathematics; understanding draft